Ways of improving efficiency process orthosawing wood processing a full duty cycle - Burdyak, Myhaylo; Kapral, Yuriy; Levytskyy, Roman; Nalyvayko , Volodymyr (Forestry, Forest, Paper and Woodworking Industry, 2017)
The efficiency of work of orthogonal circular saw machines with moving saw blade is analyzed and possibility of their work with a full working cycle of sawing of logs is noted. The features of orthosawing logs are considered with circular saws and the main defects of the machine with passing feed are determined. A way of improving the orthogonal circular saw machine with a moving saw blade is proposed in order to increase the productivity and accuracy of its work. The scheme is given and a description of the advanced machine tool is provided, which will ensure the sawing of logs with a full working cycle only with counter feed.